2023
DOI: 10.1002/cphc.202300089
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemical and Physical Properties of Organic Solvents on the Gas and Hydrogen Formation during Laser Synthesis of Gold Nanoparticles

Abstract: Laser ablation in liquids has been established as a scalable preparation method of nanoparticles for various applications. Particularly for materials prone to oxidation, it is established to suppress oxidation by using organic solvents as a liquid medium. While this often functionalizes the nanoparticles with a carbon shell, the related chemical processes that result from laser-induced decomposition reactions of the organic solvents remain uncertain. Using a systematic series of C 6 solvents complemented by n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 113 publications
(215 reference statements)
2
17
0
Order By: Relevance
“…[29] Similar findings have been reported by Marzun et al [32] , who suggested that the formation of structures with a graphite layer on the Cu NPs' surfaces is probably due to the pyrolysis of the acetone. Recently, Fromme et al [40] performed LAL with a systematic series of organic solvents and deduced selection rules for solvents that influence the formation of carbon shells.…”
Section: Resultsmentioning
confidence: 99%
“…[29] Similar findings have been reported by Marzun et al [32] , who suggested that the formation of structures with a graphite layer on the Cu NPs' surfaces is probably due to the pyrolysis of the acetone. Recently, Fromme et al [40] performed LAL with a systematic series of organic solvents and deduced selection rules for solvents that influence the formation of carbon shells.…”
Section: Resultsmentioning
confidence: 99%
“…G4 concerns the chemical and physical properties of the most abundant solute: (P29) MW, (P30) # of atoms in the molecules of solute, (P31) % of O + Cl + CN + S in the molecules of solute, (P32) minimum bond energy (kJ/mol), (P33) average bond energy (kJ/mol) of the molecules of the solute, (P34) maximum electron affinity (eV), (P35) minimum ionization potential (eV) of molecular species expected from the fragmentation of the solute, and (P36) mass fraction of the solute in the solution. When no solutes are explicitly reported, either oxygen from the atmosphere or the inert gas bubbled in the liquid (if any) was considered as the relevant solute. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Finally, we note that although our results suggest that common ablation processes drive product formation across diverse classes of organic liquids, the specific molecular structure of the liquid likely plays an important role in the distribution of ablation products. Recent observation of substantial differences in the yields of H 2 and other gaseous products during ablation of gold in n-hexane, iso-hexane, and cyclohexane 19 motivates the further exploration of how the molecular structure of the liquid impacts reactivity during ablation.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition to metal nanoparticles, gaseous products including H 2 , CO, CH 4 , C 2 H 2 , C 2 H 4 , C 2 H 6 , C 3 H 4 , C 3 H 6 , C 3 H 8 , and C 4 H 10 have been reported during LAL of a gold target. 18,19 Ablation of neat organic liquids also forms diverse products ranging from the small molecules H 2 , CH 4 , and C 2 H 2 20−23 to fluorescent carbon dots 20,24−30 and nanodiamonds. 31−33 Aromatic products including toluene, phenol, phenylacetylene, and biphenyl have been reported from ablation of benzene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation